Participant-Reported Experiences of Conversations about Sexually Transmitted Infections with Romantic Partners: Perceptions of Ownership and Privacy. Issue 5 (16th April 2023) - Brannon, Grace Ellen; Ray, Madison A.
ABSTRACT: Sexually transmitted infections (STIs) affect millions of people annually, costing 16 billion in direct costs each year. Young adults often avoid communicating with their romantic partners about STIs for fear of stigma, thereby limiting their own and their partners' ability to make informed and accurate health decisions. Using Communication Privacy Management theory as the theoretical framework, this study investigates how young adults in romantic relationships communicate about STIs with their partner. Findings show that participants report having conversations about STIs, but do not engage in regular STI testing, thereby limiting their ability to provide accurate information. They also discuss STIs in general rather than the communicating about their own history with STIs, being tested for STIs, or discussing STI test results with their partners. Practical and theoretical implications are discussed.